Explaining Governors' Response to the COVID-19 Pandemic in the United States - Leonardo Baccini; Abel Brodeur (Institute of Labor Economics (IZA), 2020)
What is the response of US governors to the COVID-19 pandemic? In this research note, we explore the determinants of implementing stay-at-home orders, focusing on governors' characteristics. In our most conservative estimate, being a Democratic governor increases the probability of implementing a stay-at-home order by more than 50 percent. Moreover, we find that the probability of implementing a statewide stay-at-home order is about 40 percent more likely for governors without a term limit than governors with a term limit. We also find that Democratic governors and governors without a term limit are significantly faster to adopt statewide orders than Republican governors and governors with a term limit. There is evidence of politics as usual in these unusual times.
Keywords: H51; I15; P16; 330; COVID-19; pandemic; ideology; governors; United States